Pięcioksiąg w Biblii. Analiza struktury retorycznej kanonu - Stanek, Teresa (Poznańskie Studia Teologiczne, 2011)
Biblical canons reflect the theology of communities that are responsible for their final shape. A majority of texts that were written during the biblical and early postbiblical period belong to a few communities and are collected in different canons. The present article considers two of them: the Hebrew Bible and the Catholic Old Testament, from the perspective of the Pentateuch, with the aim of grasping some of the doctrinal differences between early Christianity and Rabbinic Judaism. The canon of the Hebrew Bible is totally oriented towards the Pentateuch and accentuates messianic hope, but is completely closed towards any new text, contrary to the canon of the Old Testament. The Old Testament is open towards New Testament by the rearrangement of basic writings contained in the Hebrew Bible.